Estrategias para la Reactivación Económica de la Empresa Lucho Motos Neiva (2021)
What is sought with this research is to detect the difficulties that arose in the LUCHO MOTOS NEIVA company as a result of the economic crisis triggered by the COVID-19 pandemic, as of December 2020. This research will be approached from the quantitative approach, and it will be descriptive, since it seeks to systematically show the characteristics of the object of study. Therefore, the objective is to evaluate the financial statements of the periods from 2018 to 2020 through a financial analysis where the horizontal and vertical analysis was taken as the focus to see the development of the company during the health emergency, show what changes the pandemic produced in the company using financial indicators, which are made up of: Liquidity, efficiency, indebtedness and profitability so that in this way we can implement a final strategy for the economic reactivation of the LUCHO MOTOS NEIVA company.